2010
DOI: 10.1103/physrevb.81.205308
|View full text |Cite
|
Sign up to set email alerts
|

Finite size and intrinsic field effect on the polar-active properties of ferroelectric-semiconductor heterostructures

Abstract: Using Landau-Ginzburg-Devonshire approach we calculated the equilibrium distributions of electric field, polarization, and space charge in the ferroelectric-semiconductor heterostructures containing proper or incipient ferroelectric thin films. The role of the polarization gradient and intrinsic surface energy, interface dipoles, and free charges on polarization dynamics are specifically explored. The intrinsic field effects, which originated at the ferroelectric-semiconductor interface, lead to the surface ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 40 publications
2
46
0
Order By: Relevance
“…The analysis in this case is similar to that of Morozovska et al 10 Under zero applied field, as L increases, solutions 1 and 3 above involve higher and higher potentials and eventually reach regime II. There are three possible solutions:…”
Section: A Low Dopingsupporting
confidence: 77%
See 1 more Smart Citation
“…The analysis in this case is similar to that of Morozovska et al 10 Under zero applied field, as L increases, solutions 1 and 3 above involve higher and higher potentials and eventually reach regime II. There are three possible solutions:…”
Section: A Low Dopingsupporting
confidence: 77%
“…Zubko et al 8 modified the coefficients of the Devonshire-Ginzburg-Landau theory and introduced the notion of effective polarization to account for space charges. Recently, Baudry,9 using a discrete approach, as well as Morozovska et al, 10 extending the Devonshire-Ginzburg-Landau, have developed a coupled field theory of space charges and polarization, but make a priori assumptions on the space charge distribution when studying specific problems. Gureev et al 11 have studied head-to-head domain walls, while Eliseev et al 12 and Maksymovych et al 13 have studied static and dynamic conductivity of domain walls.…”
Section: Introductionmentioning
confidence: 99%
“…234,[385][386][387] In parallel, the properties of spatially separated ferroelectric-semiconductor systems were explored as driven by FeFET and FeRAM applications. [388][389][390][391][392][393] Much of these results are summarized in an excellent recent review by Hong et al 393 However, recent studies have demonstrated that in ambient conditions the screening is ionic in nature, and hence polarization dynamics at open surfaces should be considered as coupled surface electrochemical-bulk polarization switching process, as discussed in Section IV. Surprisingly the theory for such coupling was developed by Stephenson and Highland only recently, 229 and remained largely unused.…”
Section: Phenomenamentioning
confidence: 99%
“…49,50 ). The geometry of the problem is shown in Figure 4a, and corresponding constitutive equations are described in Supplementary Information.…”
mentioning
confidence: 99%